The Application of the Value Clarification Technique (VCT) Learning Model Assisted by Poster Media on the Learning Outcomes of Pancasila Education in Grade IV - Rani Puspita Sari; Eka Lokaria; Citra Raflesia (EDUJAVARE: International Journal of Educational Research, 2026)
Education is a conscious effort to grow and develop the potential of human resources through the learning process. This study aims to determine the significant completeness of the learning outcomes of Pancasila Education for Grade IV Students of SD Negeri 2 Srimulyo after applying the Value Clarification Technique (VCT) learning model assisted by poster media. The research method used was quantitative with pseudo-experiments in the pre-test and post-test categories. The population in this study is all grade IV students of SD Negeri 2 Srimulyo which amounted to 14 students and the research sample was class IV of 14 students, consisting of 6 males and 8 female students who were taken in saturated samples. The data collection technique uses a multiple-choice test technique. Based on data analysis, the average Pre-Test score was 54.46 and the average Post-Test score was 83.04 with a confidence level of α = 0.05 obtained by Zcount 4.46 and Ztable 1.64 because Zcalculate ≥Ztabel then, Ha was accepted and Ho was rejected. The results of the study can be concluded that the learning outcomes of Pancasila Education students in grade IV of SD Negeri 2 Srimulyo after applying the Value Clarification Technique (VCT) learning model assisted by poster media are significantly complete.